Simultaneous Determination of Four Active Flavonoids in Citrus Changshan Huyou Fruit Collected in Various Seasons by HPLC Method - Song, Jian-Feng; Feng, Jing-Qian; Hu, Jian-Hua; Xu, Li-Ping; Fu, Hou-Dao (Asian Journal of Chemistry, 2015)
An HPLC method was developed for the simultaneous determination of narirutin, naringin, hesperidin and neohesperidin to investigate active ingredients in citrus Changshan Huyou fruit collected in different harvest time. The solid phase was Agilent ZORBAX SB-C18 (250 mm × 4.6 mm, 5 μm), with isocratic elution using 0.2 % phosphoric acid solution-acetonitrile (85:15) as the mobile phase. The flow rate was 1 mL/min and the wavelength was 284 nm. The methodology all fit the analytical requests and the recoveries were 98.83-99.05 %. Quantitative analysis showed that the contents of four main flavonoids would change within the growth period. The contents of naringin and narirutin presented a decreasing trend after the two months' increasing, reached the highest in June. Meanwhile, the contents of neohesperidin and hesperidin appeared a downgrade trend during the growing period. The contents of naringin and neohesperidin met the requirements of Chinese pharmacopoeia during May and July. Based on the method, quantitative analysis is simple and rapid, accurate and reliable, which was suitable for the contents determination and was able to provide reference for determining the best harvest period of ChangShan-HuYou as the medicinal resource.